THE PHENOTYPE OF PREMONITORY SYMPTOMS AND MIGRAINE HEADACHE TRIGGERED WITH NITROGLYCERIN. Issue 12 (15th November 2016) - Karsan, N; Bose, P; Lowe, JT; Goadsby, PJ
Abstract : The migraine attack starts hours to days before pain onset. Given capturing this early stage during spontaneous attacks is challenging, triggered attacks offer insights into this phase of migraine. Subjects ( n =30) with migraine who reported premonitory symptomatology during spontaneous attacks were screened and recruited following informed consent. Each subject was exposed to a 0.5 mcg/kg/min nitroglycerin infusion over 20 minutes. Symptoms and timelines to development of premonitory and headache phases were recorded. 100 % of subjects developed NTG-related headache 1–10 minutes into the infusion. 97% of subjects developed premonitory symptoms 4–136 minutes after the infusion start (mean 35 minutes). 83 % of subjects developed a migraine headache within 4.5 hours of infusion (range 21–278 minutes after infusion start, mean 104 minutes); these all responded within 2 hours of 1 g intravenous aspirin or 6 mg subcutaneous sumatriptan. Typical aura was triggered in 13 %. The commonest premonitory symptoms were tiredness (73 %), photophobia (70 %) and concentration difficulty (60%). 90% reported three or more premonitory symptoms. At least one cranial autonomic symptom was triggered in 47%; the most common were a sensation of throat swelling and aural fullness. We demonstrate that NTG effectively triggers migraine premonitory symptoms even without headache, and can trigger cranial autonomic symptoms. The subjects in whom headache was triggered are now taking part in the imaging phase of the study, during which functional MRI scanning is performed at four intervals on three separate visits, to understand the brain activation changes during each stage of the attack, in a double-blind placebo-controlled fashion.